The Quintessence of Sales What You Really Need to Know to Be Successful in Sales - Hase, Stefan (Quintessence Series,, 2018)
This book from the Quintessence series offers essential know-how on the theory and practice of sales, the main turnover and value driver of any business. Sales can be seen as the "front line" where key business successes are prepared and put into practice. Sales managers and salespeople, but also professionals from production, technology, and marketing will benefit from the concise presentation of the relevant topics. Having read this book, you should have a good understanding of the key stages of the sales process from acquiring new clients (or selling to old ones) to closing the deal, and be familiar with the most typical sales performance issues described here. Moreover, in order to create a strong sales environment, you will know which qualities are needed both by sales leaders and ideal salespersons, and how to build a winning sales team and a high-quality sales organisation. Finally, by applying the principles of sales-centric business management, you will be readily equipped for immediate and lasting sales success.